The methods of assessment of postpartum hemorrhage in Ira - Afshari, porandokht; Soltani, hoora; Abedi, parvin; Kianfar, mahboobeh (Advances in Nursing & Midwifery, 2015)
Abstract Background and aim: Every year many women lose their lives because of postpartum bleeding in developing countries including Iran. Inaccurate assessment of postpartum bleeding can cause delay in treatment and further loss of blood. This study designed to investigate the methods of assessment of postpartum bleeding in Iran Materials and methods: This survey is cross sectional study that conducted in 129 obstetric units in 23 provinces in 213. To select centers, to cluster sampling, 23 of the 31 provinces in the country were enrolled. In the Provinces ,Centers of public hospitals, educational , private and obstetric centers were selected randomly. A questionnaire consisting of two sections for vaginal delivery and cesarean section was used for data collection. data analyzed by SPSS software version 19 and Descriptive statistics. Findings: Most and least used method for assessing blood loss in normal vaginal delivery was, clinical estimate (93%) and special bag for collecting blood (3/9%). Also in Cesarean delivery , Clinical estimation (81/8%) and transparent bags of blood collection (3/03%) were the least way. Conclusion :The visual estimation is the most widely method for estimation of blood loss after birth Key words: postpartum hemorrhage assessment methods, third stage of labor, postpartum hemorrhage